2020
DOI: 10.1007/s12042-020-09254-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Impacts the Response of Coffea canephora to Decreasing Soil Water Availability

Abstract: Climate change is expected to result in more frequent periods of both low rainfall and above normal temperatures for many coffee growing regions. To understand how coffee reacts to such change, we studied the physiological and gene expression responses of the clonal variety C. canephora FRT07 exposed to water deficits under two different temperature regimes. Variations in the timedependent impact of water deficits on leaf stomatal conductance and carbon assimilation were significantly different under the 27°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The present study demonstrated that water deficit alters the transcriptome profile in the two coffee genotypes. Thousands of expressed genes were identified and annotated (Figure 1; Table S1) in agreement with previous drought studies in coffee [29,52,53]. However, contrary to those studies, we examined the effects of a long-term drought experiment in which stress has been imposed gradually.…”
Section: Impacts Of Water Deficit On the Transcriptomic Profile Of Coffea Canephora (Cl153) And C Arabica (Icatu)supporting
confidence: 67%
“…The present study demonstrated that water deficit alters the transcriptome profile in the two coffee genotypes. Thousands of expressed genes were identified and annotated (Figure 1; Table S1) in agreement with previous drought studies in coffee [29,52,53]. However, contrary to those studies, we examined the effects of a long-term drought experiment in which stress has been imposed gradually.…”
Section: Impacts Of Water Deficit On the Transcriptomic Profile Of Coffea Canephora (Cl153) And C Arabica (Icatu)supporting
confidence: 67%
“…40% C. canephora [1]. However, the production of C. canephora is threatened by climate change, as it is sensitive to both water deficit and high temperature [2]. The selection of superior genotypes for adverse environmental conditions and the evaluation of diverse genetic pools are therefore essential to ensure its sustainability [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For the first one, which corresponds to 55.40 % of the data variation, Catiguá MG3 P51, Catiguá MG1, Catiguá MG3 P5, Pau Brasil MG1 and Topázio MG1190 stood out, with higher values for stomatal conductance, net photosynthetic rate and intercellular CO 2 concentration (Figure 1; Table 4). Higher stomatal conductance scores can favor the necessary substomatal CO 2 assimilation for photosynthesis (Thioune et al 2020). According to the canonical variable analysis, a positive correlation between these characteristics and the photosynthesis ratio was observed (Table 4).…”
Section: Resultsmentioning
confidence: 93%